The Role of Company Size and Board of Commissioners on Company Value in Disrupted Economics - Hisar Pangaribuan; Harsono Yoewono; Wing Wahyu Winarno (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2023)
The Covid-19 condition that has passed has provided many important lessons and has disrupted the performance and productivity of almost all industries, including manufacturing companies. Such condition has become a challenging task for companies to find solutions to maximize company value to survive, let alone increase in these conditions. Bad like that. This research aims to confirm whether company size, board of commissioners, and Covid-19 conditions significantly affect company value. By taking data from manufacturing companies during the past two years of research during the Covid-19 period, this study uses a descriptive quantitative approach with multiple linear regression analysis techniques and modeling Covid-19 as a moderator. This study uses a purposive sampling method to select manufacturing companies on the Indonesia Stock Exchange. The research data spans two years upon 159 companies, resulting in 318 data points. The research results show that the variables of company size and board of commissioners do not significantly affect company value, but Covid-19 can significantly influence company value. Covid-19 then moderated the company size and board of commissioners variables, and it was discovered that the company size and board of commissioners variables had a significant influence on company value; this demonstrates that Covid-19 has had a devastating effect on company value.